Literature Review: SWOT Analysis of Bangladesh's Key Water Policy Documents - Dewan, Camelia (2012)
Water is one of the most critical problems in Bangladesh. The Government of Bangladesh (GoB) acknowledges water as a finite resource with tremendous importance for the environment and livelihoods in its National Water Policy (GoB, 1999). The National Water Policy provides a comprehensive policy framework for pressing water issues in Bangladesh such as river basin planning, water rights and allocation, delineation of public and private domains, water supply and sanitation, preservation of the natural environment and the developmental concerns of fisheries, navigation and agriculture. The policy also provides guidance on its economic and financial management (water pricing), participation by stakeholders, decentralized management and delivery structures. In essence, the NWP is the cornerstone that guides water management in the polders of coastal Bangladesh. This SWOT analysis attempts to investigate the strengths, weaknesses, opportunities and threats of the NWP from 1999. Based on the findings from this SWOT-analysis, G3 is enabled to design its own research activities in a way that examines how policy is being translated into practice in the coastal areas. The ultimate aim of such a research approach is to share the findings with the Government of Bangladesh through participatory dissemination workshop both at polder and central levels.